Identification of the Powdery Mildew Resistance in Chinese Wheat Cultivar Heng 4568 and its Evaluation in Marker-Assisted Selection - Gao, Huiming; Xu, Xiaozhe; Ai, Pengfei; Luo, Fuyi; Guo, Peng; Ma, Pengtao (Frontiers in Genetics, 2022)
Powdery mildew induced by Blumeria graminis f. sp. Tritici (Bgt) has a devastating impact on the yield and quality of wheat in the world. Host resistance is the most effective and economical means to control this disease. In this study, an elite wheat cultivar Heng 4568 showed high resistance to 12 Bgt isolates from different regions of China at the seedling stage. Genetic analysis demonstrated that the powdery mildew resistance in Heng 4568 was conferred by a single dominant gene, temporarily designated PmH4568. PmH4568 was then mapped to the reported Pm2 interval on chromosome 5DS using five Pm2 linked markers and flanked by the markers Bwm20 and Bwm21 with genetic distance 0.3 and 0.6 cM, respectively. To further verify the relationship between PmH4568 and Pm2, the diagnostic marker Pm2b-map-3 of Pm2 was used to genotype the F2:3 families crossed by Heng 4568 and Daimai 2173, and no recombination was found, indicating that PmH4568 is also probably a Pm2 allele. To trasfer PmH4568 using marker assisted selection, the five closely linked markers and the diagnostic marker were evaluated for applicability in tracing the PmH4568 in 16 wheat cultivars from different agro-ecological area of China, and all of them can trace PmH4568 in all the detected genetic backgrounds.